Impacts of awareness towards environment among the students in UTM Skudai Johor Bahru / Nurul Syairah Sukri - Sukri, Nurul Syairah (Faculty of Business and Management, 2018)
The Universiti Teknologi Malaysia (UTM) is steadily progressing towards becoming more “green” or environmentally-friendly, but are the students really interested in the effort? They should have a good attitude and have ethics where they should know what is good and what is wrong. From the previous research, the development of environmentally sensitive attitudes among students is important for the development of positive environmental behaviors in later life (Zaleznik, 2012). Therefore, this study aims to examine the improvement of human’s health, the connected society and the reduce of pollution and clean environment towards the environment awareness and practices among students in UTM. This study is using questionnaires and will be distributed to 361 students from different level education at UTM Skudai Johor Bahru. From the result of the study, it shows that connecting to the society and nature is the most significant impact that contribute to the environmental awareness and practices of among students UTM Skudai Johor Bahru. Analysis of this resume has been done using SPSS version 23.